Depression, anxiety and stress level of type-2 diabetes mellitus patients from a selected primary care clinic in Kuantan, Pahang - Md Aris, Mohd Aznan; Tin, Myo Han (2014)

(untitled)
Introduction: Modern stressors such as financial worries, deadline pressures at work or school, as well as unnecessary physical stressors such as excessive caloric intake, obesity, and inactivity chronically activate the hypothalamic-pituitary-adrenal axis, leading to adverse health consequences such as increased rates of cardiovascular diseases, diabetes, and mood disorders like depression and anxiety. The relationship between chronic stress, depression, and anxiety is complex and incredibly powerful. Based on the facts, stress, anxiety and depression might affect together on patients with DM through physiological mechanism and via health related behavior particularly poor compliance of treatment and diet control.